Efek Mediasi Kepuasan Kerja Karyawan pada Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Pada PT. Laundry Pro - Okto, Joni; Yudhinanto, Yudhinanto; Alie, Maria Septijantini; Surya , Andi; Desmon, Desmon; Vilta, Eka Travilta Oktaria (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze the relationship between leadership style and organizational culture on employee performance through employee job satisfaction at PT. Laundry Pro. Research methodology: The research method used in this study is a quantitative method. In this study, inferential analysis was carried out using a variant-based structural equation test or Partial Least Square-Structural Equation Model (PLS-SEM). The population in this study were all employees at PT. Laundry Pro Express, totaling 132 employees. Results: based on the data analysis that has been carried out, it is revealed that leadership style has a positive and significant effect on employee job satisfaction, organizational culture has a positive and significant effect on employee job satisfaction, leadership style does not have a significant effect on employee performance, organizational culture does not have a significant effect on employee performance, employee job satisfaction has a positive and significant effect on employee performance at PT. Laundry Pro. Then employee job satisfaction is able to mediate the relationship between leadership style and organizational culture on employee performance positively and significantly. Limitations: This study is limited to only examining employee performance through leadership style, organizational culture, and employee job satisfaction, further research can examine more broadly related to variables and research objects with a larger Company scale. Contribution: This study provides suggestions for PT. Laundry Pro, in an effort to improve employee performance, not only improve leadership style and organizational culture, but must be accompanied by an increase in employee job satisfaction as well, so that it can maximize the increase in employee performance in the company.